Partial reduction of NO to N2O on Cu{311}: role of intermediate N2O2. Issue 9 (21st March 2022) - Sitathani, Krit; Jenkins, Stephen J.; Temprano, Israel
Abstract : Reflection absorption infrared spectroscopy (RAIRS) and first-principles density functional theory (DFT) combine to suggest a pathway for NO x reduction on Cu{311} involving a flat-lying N2 O2 intermediate. Abstract : We investigate the adsorption and reaction of NO on Cu{311} via a combination of reflection absorption infrared spectroscopy (RAIRS) and first-principles density functional theory (DFT), providing a mechanistic understanding of the reaction as it progresses. Our results support an interpretation that N2 O is formed via an associative mechanism involving N2 O2 as the crucial intermediate species. Consistent with previous work, we find that such an intermediate readily converts between its initial nitrogen-down configuration and an inverted oxygen-down configuration, prior to decomposition by cleavage of a single N–O bond. As the reaction proceeds, the surface is progressively poisoned by the accumulation of O adatoms resulting from N–O bond scission, and we probe this aspect of the reaction in detail as a function both of temperature and of the surface's pre-exposure to oxygen. Our results indicate that sustained conversion of NO to N2 O on Cu would be contingent upon identifying some co-reactant capable of continuously removing O from the surface as the reaction proceeds.